PENGARUH PENGANGGURAN TERHADAP KEMISKINAN DI KABUPATEN BANGKA TAHUN 2009-2018 - Gebila Gebila; Ayu Wulandari (Jurnal Manajemen Kompeten, 2020)
This study is entitled The Effect of Unemployment on Poverty in Bangka Regency. The purpose of this study was to determine the effect of Unemployment on Poverty in Bangka Regency. Hypothesis testing uses simple regression analysis. The data used in this study is Time series data from 2009-2018. The data used are secondary data for the period 2009-2018. The data analysis technique used is the type of descriptive research with a quantitative approach. The results of the study that unemployment does not affect poverty in Bangka Regency.